Pendampingan Pembuatan Pupuk Organik Cair Bagi Warga Mangunsari Gunungpati Untuk Mengelola Taman TOGA Organik (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
In line with the clean and healthy lifestyle program (CHLP) that continues to be implemented in the Mangunsari area, Gunungpati District, the development of the TOGA garden in every dasawisma in the sub-district is also being carried out. The Mangunsari area has an area of ​​public facilities that have not been used intensively, so the potential to be used as a TOGA park is still very high. Mangunsari residents also have the potential to be empowered in managing an organic